Local antibiotics and bone substitutes for treating osteomyelitis - Mohd Yusof, Nazri (2022)
Delivering a high dose of antibiotics in a poorly vascularised area. via a carrier that gradually releases the antibiotic. This will lead to high efficacy less systemic side effects. Examples of antibiotic carrier include bone cement, bone substitute such as calcium sulphate and calcium phosphate, and collagen sponge. It should be used after adequate debridement of necrotic tissue and drainage of an abscess. It is a supplement of systemic antibiotic.